PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVSDN 002 SINTONG KECAMATAN TANAH PUTIH - suryani, suryani; zulkifli, zulkifli; Noviana, Edy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract. The background of this research is that the learning outcomes of students categorized IPS still low dikerenakan student still difficulty in accepting the lesson, the teacher is less engaging students in learning and teachers only use the lecture method, and students are less involved directly to determine its own penegetahuan. Of these problems need dilakuan Research Tindakn Class (PTK) with the title Application of Cooperative Learning Model Group Investigation. This research aims to improve learning outcomes IPS Grade IV SDN 002 Sintong Tanah Putih the number of students sebanayak 20 people. This research was done in two cycles, each cycle consisting of two meetings premises once daily tests. Instrument collecting data in this research is student activity sheets and activity sheets daily tests of teachers and students. Results of the data analysis activities of teachers in sikl; us first meeting I was 60.7% and the second meeting was increased to 67.8%. on siklu II meeting I was 78.5% and the second meeting increased to 89.2%. Further analysis ahsil student activity in the first cycle the first meeting and the second meeting of 58.33% increased to 70.83%. at the first meeting of the second cycle and 78.5% in the second meeting increased to 91.66%. then the results of this analysis can be summed increased student learning outcomes, it also demonstrated an average student learning outcomes in dasart score is 65 and in the first cycle to 70.5 and the second cycle increased to 76.75. The thoroughness of learning outcomes in basic score 8 people (40%), the first cycle to 16 people (80%) and an increase again in the second cycle to 18 people (90%) can thus be concluded that if implemented Cooperative Learning Model Group Investigation can improve learning outcomes IPS Grade IV SDN 002 Sintong Tanah Puti Rokan Hilir Academic Year 2014/2015Keywords: Cooperative Learning Model GI, IPS Learning Outcomes